2018
DOI: 10.5194/tc-12-1103-2018
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric influences on the anomalous 2016 Antarctic sea ice decay

Abstract: Abstract. In contrast to the Arctic, where total sea ice extent (SIE) has been decreasing for the last three decades, Antarctic SIE has shown a small, but significant, increase during the same time period. However, in 2016, an unusually early onset of the melt season was observed; the maximum Antarctic SIE was already reached as early as August rather than the end of September, and was followed by a rapid decrease. The decay was particularly strong in November, when Antarctic SIE exhibited a negative anomaly (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 44 publications
4
116
0
Order By: Relevance
“…Third, the significant influence of sea ice in regulating the transfer of wind momentum to the sSO points to the existence of intricate atmosphere-sea ice-ocean feedbacks in the system and stresses the need for their comprehensive characterization. In this context, it is notable that Antarctic sea ice, having undergone a small interdecadal increase in extent, has recently exhibited the three lowest-extent summers on record (Schlosser et al, 2018;Turner et al, 2017). While the level to which these three years might represent the start of a longer trend is presently unclear, these events emphasize that climatic changes in Antarctic sea ice are expected (Bracegirdle et al, 2018) and will impact the momentum transfer to, and dynamical response of, the sSO.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the significant influence of sea ice in regulating the transfer of wind momentum to the sSO points to the existence of intricate atmosphere-sea ice-ocean feedbacks in the system and stresses the need for their comprehensive characterization. In this context, it is notable that Antarctic sea ice, having undergone a small interdecadal increase in extent, has recently exhibited the three lowest-extent summers on record (Schlosser et al, 2018;Turner et al, 2017). While the level to which these three years might represent the start of a longer trend is presently unclear, these events emphasize that climatic changes in Antarctic sea ice are expected (Bracegirdle et al, 2018) and will impact the momentum transfer to, and dynamical response of, the sSO.…”
Section: Discussionmentioning
confidence: 99%
“…Several works have indicated that Southern Hemisphere storminess may be a major driver of the trends (or lack thereof) observed in Antarctic sea ice extent (Maksym, 2019;Matear et al, 2015;Pezza et al, 2012;Schemm, 2018;Schlosser et al, 2018;Turner et al, 2017). Climate models struggle to capture this regional and temporal variability (Hobbs et al, 2014;Lecomte et al, 2016;Zunz et al, 2013), as well as the timing of the winter expansion and summer retreat (Hobbs et al, 2014).…”
Section: Citationmentioning
confidence: 99%
“…The rise is a seamount that climbs about 4,000 m to within 1,200 m of the surface creating a semipermanent Taylor cap that brings middepth Weddell Deep Water to the surface (e.g., Dufour et al, 2017;Kurtakoti et al, 2018). In this area, the sea ice is thin in general and has low concentration even during winter months (e.g., Kurtakoti et al, 2018;Schlosser et al, 2018).…”
Section: Introductionmentioning
confidence: 99%